Theatrical direction and the production context - conversation with Marcio Abreu (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
What is the role of the theater director in contemporary theatrical arrangements? Can directing still be considered a place of power? Is it possible to think of authorship in increasingly collaborative creations in which the director doesn’t always have the final word? At what points in the creative process do direction and production meet and separate? Is it possible to think of creative systems or procedural orders that repeat themselves when creating in multicultural contexts? These are some questions that guided the talk with director Márcio Abreu in April 2024, in which the central theme was the relationship between the production context of the scene and the creative procedures of the director.
Keywords: theatrical direction; creative procedures; production context